Pengembangan Karakter Toleransi Siswa: Eksplorasi Model Pembelajaran Project Based Learning dalam Membentuk Karakter Siswa - Dongoran, Indra Maulana; Butar-Butar, Khairunnisa; Nurlaila, Nurlaila; Hadi, Anto J (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to investigate the effect of implementing the Project Based Learning (PBL) learning model on the development of students' tolerant character in the educational environment.Method – The research method used was an experiment with a pre-test and post-test control group design. The sample consisted of two randomly selected class groups: an experimental group that received PBL and a control group that received conventional learning. Data was collected through questions, questionnaires, and documentation. Hypotheses were tested using t-tests.Findings – The research results indicate a significant positive influence of the Project Based Learning (PBL) model on developing students' tolerance. The control class's mean score is 73.40, while the experimental class's mean score is 80.70, suggesting that the control class has sufficient tolerance, whereas the experimental class shows good tolerance. The significance value obtained is 0.000, confirming the influence of the PBL model. The experimental group demonstrated a higher increase in tolerance compared to the control group. These findings suggest that PBL is an effective approach for fostering students' tolerant character in schools. Research Implications – These findings underscore the effectiveness of the Project-Based Learning (PBL) model in fostering students' tolerance. Implementing PBL can enhance character education in schools by promoting peace, respect for individual differences, and social awareness in the classroom. PBL also improves students' communication skills in project tasks, leading to better learning outcomes. It is recommended to provide guidance and training for teachers on PBL implementation, ensuring they have adequate support and resources for effective application.